Generalized π Fortescue Equivalent Admittance Matrix Approach to Power Flow Solution - Dzafic,I; Pal,BC; Gilles,M; Henselmeyer,S; Sultanic,S (IEEE Transactions on Power Systems, 2014)
This paper develops a generalized admittance matrix approach in Fortescue coordinate system to solve unbalanced/unsymmetrical distribution networks including different number of phases. This generalized Fortescue $pi$ equivalent is defined in this paper for solving the heterogeneous phase, and thus Fortescue, network model. The performance of the approach is demonstrated in different model networks with number of nodes ranging between 168 and 14200. It is found that the current iteration method exploiting the decoupling in admittance matrix in Fortescue coordinate is substantially faster than the typical unbalanced three-phase solution in phase domain. The method has a significant potential for application in real time active power network management.